(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
DNA extraction and its profiling for forensic analysis is a normal practice in the 21st century. Sample preservation isa significant step for obtaining adequate data from the samples. This study has been done for comparative analysis of the preservatives used to preserve fetal tissue. The phenol-chloroform extraction methods used for the extraction and various kits by Thermo fisher were used for the controlled results. PCR amplification kit has been utilized for subsequent development. The amplification of the samples such as fetus in formalin, fetus in normal saline, fetus limb in normal saline, fetus toe in normal saline and fetus toe in formalin. DNA profiles of all the samples were generated after RT-PCR and conventional PCR. Based on those DNA profiles data, Standard deviation and mean were derived. The probability plot of samples data showed the normal distribution, so the normal distribution of the graph has been analyzed for all the samples, based on this histogram plotted and the mean pie chart. Results concluded that fetus toe in normal saline is more effective for DNA extraction than fetus limb in normal saline.